Kultur Antera, Teknik Penyelamatan Embrio dan Rekayasa Genetik untuk Menunjang Pemuliaan Tanaman Padi - Ida Hanarida Somantri; A. Dinar Ambarwati (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2001)
The success of biotechnology in developed country encourage Indonesia to use it in rice breeding program. Every technick In biotechnology has advantage and it can be used to solve a problem in a certain purpose. Embryo rescue technich solved the problem of crossing with wild species. This technick may insert a gene from one organism to another through gene  transformation technich. The anther culture technich been used on rice: Javonica, Javanica and indica. Generally, the percentage of callus induction and regeneration has great variation (1.8% - 40%). It was Influenced by the number and type of genome. The transformation of rice using microprojecty system using cry gene resulted 172 putative transgenic plants. Twenty five of them have been tested using moleculer technick and it showed t at the plants contained cry gea.   Key words: Anther culture, Embryo rescue, Rice